2014
DOI: 10.3122/jabfm.2014.04.130238
|View full text |Cite
|
Sign up to set email alerts
|

Generational Differences in Complementary and Alternative Medicine (CAM) Use in the Context of Chronic Diseases and Pain: Baby Boomers versus the Silent Generation

Abstract: Methods: This study compares CAM usage between baby boomers (n ‫؍‬ 7734) and the silent generation (n ‫؍‬ 4682) through secondary analyses of the 2007 National Health Interview Survey data. The analysis also compares chronic disease and pain status. Multivariate logistic regression models were developed to identify generational differences.Results: Although the silent generation reported twice as many chronic disease (51.3% vs 26.1%; P < .001) and more painful conditions (56.1% vs 52.2%; P < .001), baby boomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…However, little research specifically compares CAM use among baby boomers (those born between 1945 and 1964) and pre-boomers (those born before 1945). One study (18) examined generational differences in CAM use, but focused on chronic diseases that are physical (e.g., heart disease, cancer, stroke, lung disease and diabetes). Study findings indicated that even though pre-boomers report a substantially higher prevalence of chronic diseases, baby boomers report a higher use of CAM regardless of health status.…”
Section: Objectivementioning
confidence: 99%
“…However, little research specifically compares CAM use among baby boomers (those born between 1945 and 1964) and pre-boomers (those born before 1945). One study (18) examined generational differences in CAM use, but focused on chronic diseases that are physical (e.g., heart disease, cancer, stroke, lung disease and diabetes). Study findings indicated that even though pre-boomers report a substantially higher prevalence of chronic diseases, baby boomers report a higher use of CAM regardless of health status.…”
Section: Objectivementioning
confidence: 99%
“…These may be differences that are unique to a particular birth cohort or that accumulate over the lifetime. Only two studies have examined cohort differences in CAM use [13, 14]. Both reported greater CAM use in more recent cohorts, but used cross-sectional data and could not distinguish cohort effects from age and period effects (secular changes over time).…”
Section: Introductionmentioning
confidence: 99%
“…Health variables are also important. Studies consistently indicate that chronic conditions and pain are significantly related to CAM use [7, 13, 2527]. Therefore, it is reasonable to hypothesize that the growing number of people living with chronic conditions may also underlie the growing trend in CAM use [2830].…”
Section: Introductionmentioning
confidence: 99%
“…(1) CAIM therapy use is high and rising . Research suggests 12-month prevalence of any CAIM usage (excluding prayer) in the USA is around 35 – 50%; Baby Boomers (adults born from 1946 to 1964) report significantly higher rates of use than the Silent Generation (born from 1925 to 1945) for chronic conditions 26 . (2) The global population is aging .…”
Section: Clinical Advances In Geriatric Depressionmentioning
confidence: 99%